2018
DOI: 10.1002/chem.201803096
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocycle‐Fused Pentalenes by a Gold‐Catalyzed Annulation of Diethynyl‐Quinoxalines and ‐Phenazines

Abstract: The gold-catalyzed annulation of diethynyl N-heterocycles for the synthesis of quinoxaline-/phenazine-based pentalenes and the study of their optoelectronic properties are described. The inhibition of the gold catalyst by the nitrogen centers in the substrate and the product could be overcome by increasing the reaction temperature to 130 °C, which usually leads to catalyst decomposition in gold catalysis. At 130 °C, 6,7-di(arylethynyl)quinoxalines in chlorobenzene give the corresponding pentalenes. The annulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Later, some investigations with quinoxaline-/phenazine-fused pentalenes were attempted (Scheme 61). 326 Due to the coordination of such nitrogen moieties and therefore possible deactivation of the active gold catalyst, these substructures are in general problematic. In this case, a temperature of 130 °C under microwave irradiation was applied to furnish the resulting pentalene derivatives in moderate to good yields.…”
Section: Pentalenesmentioning
confidence: 99%
“…Later, some investigations with quinoxaline-/phenazine-fused pentalenes were attempted (Scheme 61). 326 Due to the coordination of such nitrogen moieties and therefore possible deactivation of the active gold catalyst, these substructures are in general problematic. In this case, a temperature of 130 °C under microwave irradiation was applied to furnish the resulting pentalene derivatives in moderate to good yields.…”
Section: Pentalenesmentioning
confidence: 99%
“…The reaction mechanism involves a vinyl cation intermediate 173 and operates under mild reaction conditions. Interestingly optical properties have been described in this kind of annulated-pentalene compounds making them potential candidates for future optoelectronic devices (Sekine et al, 2018). Another example by Hashmi et al was reported in 2017 and was highlighted as the first intramolecular trapping of dually gold-activated intermediates 176 with an olefinic C(sp 2 )-H bond (Figure 15B).…”
Section: Gold-catalyzed Isomerization Processes Involving An Initimentioning
confidence: 99%
“…For instance, the gold‐catalyzed annulation of diyne compounds enabled the synthesis of extended π‐conjugated compounds, such as azahelicene, polycyclic indole and benzothiophen derivatives . Our recent work also contributed to the gold‐catalyzed synthesis of dibenzo[ a , e ]pentalene and quinoxaline/phenazine‐fused pentalene derivatives from 1,5‐diynes . Moreover, the gold catalyst led to both U‐shaped and S‐shaped bispentalenes from the readily available tetra(arylethynyl)benzenes and ‐naphthalenes, albeit fortunately those mixtures could be separated (Scheme , top) .…”
Section: Introductionmentioning
confidence: 98%